Effects of Neuropsychological Intervention in a Child with Functional Deficit in Programming and Control - Fernanda Ochoa Cardona, M; Quintanar Rojas, L (KnE Life Sciences, 2018)
Introduction. The brain’s third functional block is considered an important element in the impairment of child development, which has been conceptually linked to ADHD and learning difficulties. Its rehabilitation presents some skepticism regarding the effectiveness of the treatments. This is associated with the lack of relationship between the established diagnosis and the intervention proposal, the lack of knowledge of the basic psychological needs of each age and the design of an intervention program that corresponds to the neuropsychological syndrome. Methodology. The main purpose of this paper is to present the results of a neuropsychological intervention in a 11-year-old schoolgirl from the city of Puebla-México with a functional deficit in programming and control mechanism. The intervention program was scheduled twice a week for 11 months; gauging its effectiveness with pre-post neuropsychological and electroencephalography (EEG) assessment. The EEG data revealed functional bilateral changes of origin in basal ganglia, mesencephalic and of the brainstem. The method of qualitative syndromic analysis of the functional status of the cerebral mechanisms was used, especially in mistakes made at different tasks associated with the mechanism involved. The program was elaborated based on the structure and content of the school learning activity and zone of proximal development. Results. A significant improvement was observed in the functional state of programming and control and improvement in school performance. Conclusion. Approaches to child correction like the cultural-historical are necessary in the neuropsychological field to generate methods that guarantee the psychological and neuropsychological development. Keywords: Neuropsychological syndrome, child neuropsychology, child neuropsychological intervention, developmental problems, subcortical structures.